Assessment of Worldwide Acute Kidney Injury, Renal Angina and Epidemiology in Critically Ill Children (AWARE): study protocol for a prospective observational study - Basu, Rajit K; Kaddourah, Ahmad; Terrell, Tara; Mottes, Theresa; Arnold, Patricia; Jacobs, Judd; Andringa, Jennifer; Goldstein, Stuart L (BMC nephrology, 2015)
Background Acute kidney injury (AKI) is associated with poor outcome in critically ill children. While data extracted from retrospective study of pediatric populations demonstrate a high incidence of AKI, the literature lacks focused and comprehensive multicenter studies describing AKI risk factors, epidemiology, and outcome. Additionally, very few pediatric studies have examined novel urinary biomarkers outside of the cardiopulmonary bypass population. Methods/Design This is a prospective observational study. We anticipate collecting data on over 5000 critically ill children admitted to 31 pediatric intensive care units (PICUs) across the world during the calendar year of 2014. Data will be collected for seven days on all children older than 90 days and younger than 25 years without baseline stage 5 chronic kidney disease, chronic renal replacement therapy, and outside of 90 days of a kidney transplant or from surgical correction of congenital heart disease. Data to be collected includes demographic information, admission diagnoses and co-morbidities, and details on fluid and vasoactive resuscitation used. The renal angina index will be calculated integrating risk factors and early changes in serum creatinine and fluid overload. On days 2–7, all hemodynamic and pertinent laboratory values will be captured focusing on AKI pertinent values. Daily calculated values will include % fluid overload, fluid corrected creatinine, and KDIGO AKI stage. Urine will be captured twice daily for biomarker analysis on Days 0–3 of admission. Biomarkers to be measured include neutrophil gelatinase lipocalin (NGAL), kidney injury molecule-1 (KIM-1), liver-type fatty acid binding protein (l-FABP), and interleukin-18 (IL-18). The primary outcome to be quantified is incidence rate of severe AKI on Day 3 (Day 3 – AKI). Prediction of Day 3 – AKI by the RAI and after incorporation of biomarkers with RAI will be analyzed. Discussion The Assessment of Worldwide Acute Kidney Injury, Renal Angina and Epidemiology (AWARE) study, creates the first prospective international pediatric all cause AKI data warehouse and biologic sample repository, providing a broad and invaluable resource for critical care nephrologists seeking to study risk factors, prediction, identification, and treatment options for a disease syndrome with high associated morbidity affecting a significant proportion of hospitalized children. Trial registration ClinicalTrials.gov: NCT01987921